Establishment of a mouse model for amiodarone‐induced liver injury and analyses of its hepatotoxic mechanism. Issue 1 (20th April 2015) - Takai, Shohei; Oda, Shingo; Tsuneyama, Koichi; Fukami, Tatsuki; Nakajima, Miki; Yokoi, Tsuyoshi
Abstract: Drug‐induced liver injury (DILI) is the most frequent cause of post‐marketing warnings and withdrawals. Amiodarone (AMD), an antiarrhythmic, presents a risk of liver injury in humans, and its metabolites, formed by cytochrome P450 3A4, are likely more toxic to hepatocytes than AMD is. However, it remains to be clarified whether the metabolic activation of AMD is involved in liver injury in vivo . In this study, to elucidate the underlying mechanisms of AMD‐induced liver injury, mice were administered AMD [1000 mg kg –1, per os (p.o.)] after pretreatment with dexamethasone [DEX, 60 mg kg –1, intraperitoneal (i.p.)], which induces P450 expression, once daily for 3 days. The plasma alanine aminotransferase (ALT) levels were significantly increased by AMD administration in the DEX‐pretreated mice, and the liver concentrations of desethylamiodarone (DEA), a major metabolite of AMD, were correlated with the changes in the plasma ALT levels. Cytochrome c release into the hepatic cytosol and triglyceride levels in the plasma were increased in DEX plus AMD‐administered mice. Furthermore, the ratio of reduced glutathione to oxidized glutathione disulfide in the liver significantly decreased in the DEX plus AMD‐administered mice. The increase of ALT levels was suppressed by treatment with gadolinium chloride (GdCl3 ), which is an inhibitor of Kupffer cell function. From these results, it is suggested that AMD and/or DEA contribute to the pathogenesis of AMD‐induced liver injury by producing mitochondrial and oxidative stress and Kupffer cell activation. This study proposes the mechanisms of AMD‐induced liver injury using an in vivo mouse model. Copyright © 2015 John Wiley & Sons, Ltd. Abstract : In this study, an in vivo mouse model of amiodarone‐induced liver injury was developed with co‐administration of dexamethasone and possible mechanisms were investigated. It was suggested that amiodarone and/or desethylamiodarone contribute to the pathogenesis of amiodarone‐induced liver injury by producing mitochondrial and oxidative stress and Kupffer cell activation. This study provides a new perspective on drug‐induced liver injury and is useful for achieving an in vivo hepatotoxicity assay in nonclinical drug development.